Managing cities at night a practitioner guide to the urban governance of the night-time economy - Acuto, Michele 1984-; Seijas, Andreina ca. 20./21. Jh; McArthur, Jenny; Robin, Enora (Bristol University Press, 2022)
Urban experts consider the future of night-time economies' governance during the pandemic and beyond in this scholarly and accessible guide. They use global case studies to illustrate a range of socio-economic issues in cities after dark, and investigate the role of public and private sectors and leaders in shaping urban planning and policy